2000
DOI: 10.1104/pp.122.4.1081
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins and Seed Development in Maize. I. Evidence That Gibberellin/Abscisic Acid Balance Governs Germination versus Maturation Pathways

Abstract: Abscisic acid (ABA) is required for the regulation of seed maturation in maize (Zea mays L.). Mutants blocked in ABA synthesis (such as viviparous-5) do not mature to quiescent, desiccationtolerant seeds, but germinate on the ear midway through kernel development. Because gibberellins (GA) and ABA act antagonistically in many aspects of plant development, we hypothesized that ABA antagonizes a positive GA signal for precocious germination in maize. In these experiments, we show that a GA deficiency early in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(136 citation statements)
references
References 41 publications
6
126
0
4
Order By: Relevance
“…The inhibition of de novo ABA biosynthesis by fluridone in the newly formed leaves of these plants caused a complete break of leaf embryo dormancy and induced their "germination." Our results are in agreement with two other reports, which showed that the applications of fluridone to developing embryos, before the increase of endogenous ABA levels, prevented both ABA accumulation and development of embryo dormancy (Fong et al, 1983;White et al, 2000). On the other hand, none of the exogenous ABA applications could aggravate the transgenic dormant seed-like phenotype, nor did they affect normal wildtype leaf embryo development (data not shown).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The inhibition of de novo ABA biosynthesis by fluridone in the newly formed leaves of these plants caused a complete break of leaf embryo dormancy and induced their "germination." Our results are in agreement with two other reports, which showed that the applications of fluridone to developing embryos, before the increase of endogenous ABA levels, prevented both ABA accumulation and development of embryo dormancy (Fong et al, 1983;White et al, 2000). On the other hand, none of the exogenous ABA applications could aggravate the transgenic dormant seed-like phenotype, nor did they affect normal wildtype leaf embryo development (data not shown).…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that ABA alone is not sufficient to induce dormancy to K. daigremontiana leaf embryos. In fact, the ABA-deficient maize mutant kernels are viviparous and precociously germinate in spite of a large contribution of ABA from the maternal plant (White et al, 2000). These results have led to the supposition that a threshold level of ABA at the appropriate time is required to block viviparous development (Fong et al, 1983;White et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These include ABA/stressinducible proteins, heat shock proteins, late embryogenesis abundant (LEA) proteins, and proteases (Yacoob and Filion, 1986;Prasad, 1996;Nieto-Sotelo et al, 1999;White et al, 2000). Upon comparing the accession numbers of drought and cold-induced genes in Arabidopsis reported by Seki et al (2001) with the differentially expressed genes in this study (Tables I-IV), we found none of the genes to be in common.…”
Section: Differentially Expressed Genesmentioning
confidence: 92%
“…The current theory of ABA/GAs antagonism in seed germination is based on experiments showing that ABA-deficient and ABAinsensitive mutants rescue the germination of the ga1 GA-deficient mutant and of seeds treated with GA biosynthetic inhibitor (Koornneef et al, 1982;Nambara et al, 1991;Leon-Kloosterziel et al, 1996). In maize (Zea mays), the ABA/GAs balance also governs seed development, as GA deficiency early in seed development suppresses precocious germination in ABA-deficient developing kernels and bioactive GA species accumulate prior to the peak in ABA content (White et al, 2000). While ABA biosynthesis is regulated both maternally and zygotically, the control of GA biosynthesis during seed development is largely unknown.…”
mentioning
confidence: 99%